{Usage of the levonorgestrel-releasing intrauterine system (LNG-IUS) in adolescence: what is the evidence so far?} - Patseadou, M.; Michala, L. (Archives of Gynecology and Obstetrics, 2017)
© 2016, Springer-Verlag Berlin Heidelberg. Purpose: The levonorgestrel-releasing intrauterine system (LNG-IUS) is an effective method of contraception, while also providing various non-contraceptive benefits. Although targeted primarily to adults, there is increasing experience in its use in adolescence. The aim of this review is to assess the available information on LNG-IUS usage in adolescence. Methods: We conducted an online search on MEDLINE and SCOPUS from inception to May 24, 2015. All studies that examined LNG-IUS use in teen populations were eligible for inclusion. Primary outcome measures included description of indications for LNG-IUS usage and relevant efficacy. Secondary outcomes included complications, such as device-related problems (perforation and expulsion) and other adverse events (pelvic inflammatory disease, PID). Acceptability of the LNG-IUS was also estimated through evaluation of continuation rate and reasons for removal were assessed. Results: Twenty-one studies met our inclusion criteria. We identified only one randomized controlled trial (RCT). All other twenty studies were observational. Pregnancy rates ranged from 0 to 2.7{%}. Management of heavy or/and painful periods was successful in 92–100{%}. Menstrual manipulation in patients with developmental delay was achieved in over 93{%} of cases. Expulsion rates ranged from 0 to 13{%} and pelvic infection/cervicitis between 0 and 2.7{%}. There were no reported uterine perforations. Conclusion: Usage of the LNG-IUS in teen populations appears to be safe and efficacious both in terms of contraception and menstrual management. However, more robust evidence is needed so as to provide firm confirmation on benefits and potential side effects.
Keywords: Adolescents; IUCD; LARC; LNG-IUS; Mirena IUS